The villainess's guide to (not) falling in love. 5 - Touya (Square Enix Manga, 2026)
Can one would-be villainess fend off multiple handsome suitors' advances to simply live a peaceful life? Or will the game force a happy ending no matter what? Romance blooms amidst battle as Luciana's dashing allies reveal their charms! When she storms the enemy's castle, Luciana is stunned to find her brother Saphir casually soaking in a bath! However, his cryptic behavior hides a fierce determination to protect her. Saphir is prepared to face the East Star alone, but Luciana won't let him go without her, and their shared bond could trigger a miracle! Plus, in the heat of battle, the gallant Commander Joshua pledges to protect Luciana--not out of duty but from the depths of his heart. Luciana may have sworn off love, but how is a girl supposed to resist when romance is lurking around every turn?